Studies in Eighteenth-Century Music: A Tribute to Karl Geiringer on his Seventieth Birthday - Geiringer, Karl 1899-1989; Landon, H. C. Robbins 1926-2009; Chapman, Roger Eddington 1916-1989 (London Allen & Unwin, 1970)
Musicology--the scientific study of music--is particularly relevant to the brilliant range of music composed in Europe within the eighteenth century. This collection of essays is both imaginative in scope and authoritative in scholarship. The works of such famous composers as Joseph Haydn, Handel, J. S. Bach and C. P. E. Bach are discussed in detail, as are the achievements of other composers of that area--Leonardo Leo, Johann Mattheson, Piccinni, Clementi and so on. The studies are dedicated to Karl Geiringer on the occasion of his seventieth birthday. Dr. Geiringer is a distinguished music scholar of Haydn and many other composers, and there is an exhaustive and selected bibliography of his works at the end of the book. Edited by Roger E. Chapman and H. C. Robbins Landon the book includes essays by Gerald Abraham, Robert Donington, Putnam Aldrich and William G. Waite, as well as many other leading American and European musicologists. It will be of immense value to all who wish to increase their knowledge of music and so heighten the appreciation of what they hear. Consistently exploratory and never repetitive in style or subject matter these essays are also of wide biographical, sociological and historical interest.
"A selected bibliography of the works of Karl Geiringer in honour of his seventieth birthday, compiled by Martin A. Silver": p. [407]-419.
edited by H. C. Robbins Landon in collaboration with Roger E. Chapman
Keywords: 18th Century (1701-1800); Music history